Fecal microbiota transplantation unveils sex-specific differences in a controlled cortical impact injury mouse model - Pasam, Tulasi; Dandekar, Manoj P. (Frontiers in Microbiology, 2024)
Contusion type of traumatic brain injury (TBI) is a major cause of locomotor disability and mortality worldwide. While post-TBI deleterious consequences are influenced by gender and gut dysbiosis, the sex-specific importance of commensal gut microbiota is underexplored after TBI. In this study, we investigated the impact of controlled-cortical impact (CCI) injury on gut microbiota signature in a sex-specific manner in mice. Firstly, we depleted the gut microflora of male and female mice using antibiotic treatment. Then male mice were colonized by the gut microbiota of female mice and vice versa employing the fecal microbiota transplantation (FMT) method. CCI surgery was executed using a stereotaxic impactor (Impact One™). For the 16S rRNA gene amplicon study, fecal boli of mice were collected at 3 days post-CCI (dpi). CCI-operated male and female mice exhibited a significant alteration in the genera of Akkermansia, Alistipes, Bacteroides, Clostridium, Lactobacillus, Prevotella, and Ruminococcus. At the species level, less abundance of Lactobacillus helveticus and Lactobacillus hamsteri was observed in female mice, implicating the importance of sex-specific bacteriotherapy in CCI-induced neurological deficits. FMT from female mice donor to male mice displayed an increase in genera of Alistipes, Lactobacillus, and Ruminococcus and species of Bacteroides acidifaciens and Ruminococcus gnavus. Female FMT-recipient mice from male donors showed an upsurge in the genus Lactobacillus, and species of Lactobacillus helveticus, Lactobacillus hamsteri, and Prevotella copri. These results suggest that the post-CCI neurological complications may be relevant to the differential gut microbiota perturbation in male and female mice.